Reverdy Johnson papers - Johnson, Reverdy, 1796-1876.
Correspondence relating chiefly to Johnson's service as U.S. senator from Maryland, as a special inquirer in the case (1862) of Gen. Benjamin Franklin Butler at New Orleans, and as U.S. minister to Great Britain. Includes material pertaining to Johnson's early law practice in Baltimore, Md. Correspondents include George Douglas Campbell, Duke of Argyll; William Cullen Bryant; Benjamin Disraeli, Earl of Beaconsfield; Stephen A. Douglas, W.E. Gladstone; Robert E. Lee; Louisa Catherine D'Arcy-Osborne, Duchess of Leeds; Jonathan D. Meredith; Charles Reade; John Osborne Sargent; William T. Sherman; Sir James Emerson Tennent; and Martin Van Buren.
Microfilm edition available
Lawyer, U.S. senator from Maryland, and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Argyll, George Douglas Campbell, -- Duke of, -- 1823-1900 -- Correspondence; Bryant, William Cullen, -- 1794-1878 -- Correspondence; Butler, Benjamin F. -- 1818-1893.; Disraeli, Benjamin, -- 1804-1881 -- Correspondence; Douglas, Stephen A. -- 1813-1861 -- Correspondence; Gladstone, W. E. -- 1809-1898 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Leeds, Louisa Catherine D'Arcy-Osborne, -- Duchess of, -- approximately 1792-1874 -- Correspondence; Meredith, Jonathan D., -- 1783-1872 -- Correspondence; Reade, Charles, -- 1814-1884 -- Correspondence; Sargent, John Osborne, -- 1811-1891 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Tennent, James Emerson, -- Sir, -- 1804-1869 -- Correspondence; Van Buren, Martin, -- 1782-1862 -- Correspondence; Diplomatic and consular service, American -- Great Britain; Practice of law -- Maryland -- Baltimore; Great Britain -- Foreign relations -- United States; Louisiana -- History -- Civil War, 1861-1865.; New Orleans (La.) -- History -- Civil War, 1861-1865.; United States -- Foreign relations -- Great Britain; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; Diplomats; Lawyers; Senators, U.S. Congress -- Maryland